2015
DOI: 10.3892/etm.2015.2634
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the clinicopathological characteristics of gastrointestinal neuroendocrine neoplasms

Abstract: Abstract. The aim of the present study was to analyze and summarize the clinicopathological characteristics and factors affecting prognosis for patients with gastrointestinal neuroendocrine neoplasms (GINENs). Retrospective analysis was conducted on the clinicopathological data of 74 patients who were diagnosed with GINEN, and immunohistochemical methods were used to detect the expression levels of relevant markers [synaptophysin (Syn), chromogranin A (CgA) and . Among the 74 cases with GINEN, there were 39 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…Immunohistochemical staining is essential for the detection of the neuroendocrine markers that are usually expressed by these tumors, including synaptophysin, chromogranin A and others, if clinically relevant [16, 17]. Treatment and prognosis depends on the size, stage, grade, resectability, and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical staining is essential for the detection of the neuroendocrine markers that are usually expressed by these tumors, including synaptophysin, chromogranin A and others, if clinically relevant [16, 17]. Treatment and prognosis depends on the size, stage, grade, resectability, and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…SCML2 expression was detected in GEP-NET tissues using immunohistochemical staining in the present study, and then SCML2 was compared with existing markers in terms of diagnostic value. At present, GEP-NETs are commonly diagnosed by the immunostaining of Syn and CgA, which are widely accepted as classic NET markers (37). In the present study, the positivity rates of Syn and CgA in GEP-NETs were calculated to be 84.4 and 71.9%, respectively, and GEP-NET tissues exhibited weak positive staining with the majority of them being rated +.…”
Section: Discussionmentioning
confidence: 91%
“…According to a study of 256 MNETs patients, individuals with local disease (primary tumor and/or locoregional lymph node metastases) exhibited a median survival of 108 months, compared to 159 months if < 5 liver metastases and 53 months if ≥5 liver metastases [26]. On the other hand, definite conclusion has already been reached that survival for distant metastatic MNETs patients was significantly worse than those without [2729]. All the above evidence showed that liver metastasis has almost the same, if not better, prognosis compared with other distant metastasis.…”
Section: Discussionmentioning
confidence: 99%